Internalisasi Nilai-nilai Moderasi Beragama dalam Pembelajaran Fikih di Madrasah Aliyah - Tanjung, Agus Salim (MAN 4 Kota Pekanbaru, 2022)
The cases of intolerance that are growing nowadays demand significant efforts from various parties. Madrasah Aliyah as an educational institution under the Ministry of Religious Affairs of the Republic of Indonesia which has a special distinction in teaching Islamic Religious Education has the responsibility to find out the alternatives to this problem. Therefore, this study aims to describe the design of internalizing religious moderation values in Fiqh learning at Madrasah Aliyah as a deradicalization effort. This study was carried out using a qualitative descriptive approach to get a complete picture of the various theories. In addition, sources of data from multiple pieces of literature were collected through documentation and analyzed using content analysis techniques. This study recommends that religious moderation values be internalized in Fiqh learning through at least four strategies: integration in learning plans, integration in learning materials, integration in the learning process, and integration in learning evaluation.